Fiber optic sensors type LPG applied to the determination of stresses and deformations in soils - Mosquera, Luis (2018)
This paper shows the application of LPG optical fiber sensors to the determination of the transmitted stress and deformation of a sample of confined soil subjected to surface loads. The transmitted stress was measured by a mechanical LPG pressure sensor and the curvature of the ground by permanent LPG sensors buried at depths of 0.1m; 0.2m; 0.4m and 0.6m. Clay-sandy soil characteristic of UNICAMP was deposited in a cylinder of 0.8m in length and 0.30m in diameter. The soil was lightly compacted in 0.2m layers and an LPG sensor was installed on each layer. Surface loads of up to 227 KPa were applied to the surface of the soil, measuring axial soil deformations of less than 3mm by our sensors with sensitivities of the order of 0.22 mm/dB. The values of the modulus of elasticity for this type of soil were determined from the fitting of the Bousinessq equations with the values measured by the buried LPG sensors. A Young's modulus of 5.39 MPa and a Poisson's coefficient ν = 0.52 were determined for this type of soil.